Land-use governance: The interplay of social, market, and policy drivers – A global systematic review - Elsa L. Dingkuhn; Lilian O'Sullivan; Caitlin A. Grady; Erik de Klerk; Rogier P.O. Schulte (Earth System Governance)
Sustainable land-use governance is challenged by the complex interplay of local to global influences. This study combines two complementary approaches: a systematic review compiling a database of direct and diffuse contextual land-use drivers; and a cross-case analysis of three contrasting contexts: Ireland (regulated EU), Pennsylvania (market-driven US), and the Philippines (emerging economy) to uncover systemic interactions between drivers within and across cases.Among direct drivers, regulatory approaches had the greatest impact, especially when synergistically combined with softer instruments. Market drivers highlight the need to engage supply-chain actors beyond farmers. Contextual factors outweighed direct drivers: farmers’ choices remain rooted in social contexts on which governance instruments depend for their effectiveness.We demonstrate the need for greater policy coherence by addressing conflicting influences that hinder policy objectives, integrating socio-cultural and structural factors, and prioritising context-sensitive approaches. Amidst escalating ecological pressures, we provide recommendations and common governance principles applicable across diverse institutional settings.